The Modernist Exceptional Merits in The Architecture of Qahtan Al-Madfai - Sultani, Ali Saadoon; Ali, Saba Sami Al (Al-Nahrain Journal for Engineering Sciences, 2025)
In the last two decades Modern architecture of the 20th century has become a primary focus for numerous global organizations, researchers, and academics who aim to preserve and sustain it. The leading parties in this endeavor are UNESCO and the International DOCOMOMO. They recognize modern heritage as tangible, authentic, carrying exceptional features and modern characteristics that reflect values, shifts, and norms of its era. Therefore, Docomomo has identified key Modernist Merits as criteria to assess the authenticity of this heritage, while UNESCO has listed many modern buildings and sites on the World Heritage List. In this respect many Iraqi modernist buildings suffer from mishandling and poor interest. Numerous have been distorted, demolished, or are on the verge of disappearing. This reflects a lack of understanding their exceptional modernist values which are worthy of preservation, and thus inefficiency in managing this heritage. Given that Intervention in modernist heritage involves adhering to guidelines set by international organization, the vague connection between criteria of DOCOMOMO and those of UNESCO clouds the process. Therefore, this article focuses on addressing the relationship between the two organizations' sets of criteria and clarifying their connection. The authors also aimed to address the national Iraqi context by assessing selected cases of modernist heritage buildings by one of Iraq’s modernism pioneers, architect Qahtan Al-Madfai, against DOCOMOMO’s criteria for modernist merits, highlighting the originality of Iraqi modernist heritage.Using a descriptive analytical approach, the theoretical sections of the paper begin by exploring the principles and characteristics of modern architecture, followed by identifying the exceptional values of modernist buildings, defined by DOCOMOMO as Modernist Merits and linking them to UNESCO's criteria. The practical part includes an experts’ survey to assess the Modernist Merits of the selected sample of Al- Madfaies’ buildings.The research results showed that Qahtaan Al-Madfai’s architecture was distinguished by a high evaluation of two Merits (exceptional features): the technological feature and the artistic aesthetic feature. While the first was fairly preserved, the second feature was affected in some buildings as a result of the mismanagement of these buildings and the lack of awareness of their values.